Piscina Municipal - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observo la Piscina Municipal hoy conocido como Parque Zonal de Iquitos. Sucreacion tiene la finalidad de promover las diferentes actividades deportivas de la Región Loreto sus provincias y distritos.
ENGLISH: It was observed the Municipal Swimming Pool today known as Zonal Park of Iquitos. Sucreacion has the purpose of promoting the different sports activities of the Loreto Region, its provinces and districts.

SPANISH: Se observo la Piscina Municipal hoy conocido como Parque Zonal de Iquitos. Sucreacion tiene la finalidad de promover las diferentes actividades deportivas de la Región Loreto sus provincias y distritos.
ENGLISH: It was observed the Municipal Swimming Pool today known as Zonal Park of Iquitos. Sucreacion has the purpose of promoting the different sports activities of the Loreto Region, its provinces and districts.
Municipal Swimming Pool
Keywords: Iquitos (Perú)|~|Park and sports centers|~|Swimming pools|~|Perú|~|Pool|~|Iquitos (Perú)|~|piscina|~|Perú|~|parque y polideportivo|~|piscina|~|Perú|~|piscina|~|Iquitos (Perú)|~|swimming pool|~|Peru|~|park and sports center|~|swimming pool|~|Peru|~|pool